The implementation of an external ventricular drain care bundle to reduce infection rates. (3rd March 2020) - Talibi, Sayed Samed; Silva, Adikarige HD; Afshari, Fardad T.; Hodson, James; Roberts, Stuart AG; Oppenheim, Beryl; Flint, Graham; Chelvarajah, Ramesh
Abstract: Background: The main complication of external ventricular drains (EVD) is infection. Implementation of evidence-based guidelines for central venous catheter (CVC) care resulted in significant declines in infections. We tested a comparable approach to EVD infection rates. Methods: An initial retrospective study evaluated the existing EVD infection rate, and identified contributory risk factors. Based on our results, and in corroboration with existing literature, an EVD care bundle was developed and implemented. A prospective study was then conducted to identify improvement. Results: A total of 275 EVDs (120 pre- and 155 post-EVD care bundle) inserted over a period of 1532 days were included. Pre-care bundle, the infection rate was 27%, with the predominant factor associated with infection being number cerebrospinal fluid sampling episodes. Following introduction of the EVD care bundle, the infection rate declined to 10% ( p < 0.001) with the incidence from 21 to 9 cases per 1, 000 EVD-days ( p = 0.003). The infection rate was not found to be significantly associated with the number of accesses during this period ( p = 0.910). Conclusions: Introduction of a well-implemented EVD care bundle can significantly decrease EVD infection rates.